On Jensen-Related Inequalities for Various Types of Convexity via a Unified Approach - Shoshana Abramovich (Axioms)
The focus of this paper is on three types of convexity: generalized uniform convexity, <semantics>Φ</semantics>-convexity and superquadracity. The similar structures of these types of convexity are such that the same processes can be applied to each one of them to obtain further refinements of known inequalities.